Dialogue and transformation: embracing sexual diversity in the educational context - Moscheta, Murilo dos Santos; McNamee, Sheila; Santos, Jucely Cardoso dos (Educar em Revista, 2011)
<!–[if gte mso 9]> Normal 0 21 false false false MicrosoftInternetExplorer4 <![endif]–><!–[if gte mso 9]> <![endif]–><!–[if !mso]> <mce:style><! st1\:*behavior:url(#ieooui) –> <!–[endif]–><!–[if gte mso 10]> <mce:style><! /* Style Definitions */ table.MsoNormalTable mso-style-name:"Tabela normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-parent:""; mso-padding-alt:0cm 5.4pt 0cm 5.4pt; mso-para-margin:0cm; mso-para-margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:10.0pt; font-family:"Times New Roman"; mso-ansi-language:#0400; mso-fareast-language:#0400; mso-bidi-language:#0400; –> <!–[endif]–> Although recent policies in education in Brazil have included sexuality as an important theme to be discussed in the classroom, it still has not effectively created an educational context where sexuality can be discussed in a positive, non-discriminatory and culturally/historically sensitive way. This article aims at contributing to the development of training programs for sexual educators, specifically for those who are concerned with the inclusion of non-normative sexualities in the educational context. Drawing on social constructionist ideas, we have delineated a model for a training program for sexual educators in which two themes – relational engagement and focus on the process – set the context for a transformation in education. First, we offer a brief review of sexual education in Brazil. Next, we introduce the notion of “intelligibility communities” and “dialogue,” as useful concepts for exploring educational alternatives. These two concepts allow us to discuss how values are generated and how they play into our accounts about what we consider to be real and good. Finally, inspired by one of our training programs, we illustrate some ways in which these theoretical resources can be used in training activities. Keywords: sexual education; gender and sexuality; teacher training; dialogue; social constructionism.